Preventive Inositol Hexaphosphate Extracted from Rice Bran Inhibits Colorectal Cancer through Involvement of Wnt/β-Catenin and COX-2 Pathways. (24th October 2013) - Shafie, Nurul Husna; Mohd Esa, Norhaizan; Ithnin, Hairuszah; Md Akim, Abdah; Saad, Norazalina; Pandurangan, Ashok Kumar
Abstract : Nutritional or dietary factors have drawn attention due to their potential as an effective chemopreventive agent, which is considered a more rational strategy in cancer treatment. This study was designed to evaluate the effect of IP6 extracted from rice bran on azoxymethane- (AOM-) induced colorectal cancer (CRC) in rats. Initially, male Sprague Dawley rats were divided into 5 groups, with 6 rats in each group. The rats received two intraperitoneal ( i.p. ) injections of AOM in saline (15 mg/kg body weight) over a 2-week period to induce CRC. IP6 was given in three concentrations, 0.2% (w/v), 0.5% (w/v), and 1.0% (w/v), via drinking water for 16 weeks. The deregulation of the Wnt/ β -catenin signaling pathway and the expression of cyclooxygenase (COX)-2 have been implicated in colorectal tumorigenesis. β -Catenin and COX-2 expressions were analysed using the quantitative RT-PCR and Western blotting. Herein, we reported that the administration of IP6 markedly suppressed the incidence of tumors when compared to the control. Interestingly, the administration of IP6 had also markedly decreased β -catenin and COX-2 in colon tumors. Thus, the downregulation of β -catenin and COX-2 could play a role in inhibiting the CRC development induced by IP6 and thereby act as a potent anticancer agent.